2003
DOI: 10.1074/jbc.m303596200
|View full text |Cite
|
Sign up to set email alerts
|

Mapping σ54-RNA Polymerase Interactions at the –24 Consensus Promoter Element

Abstract: The 54 promoter specificity factor is distinct from 70 -type factors. The 54 -RNA polymerase binds to promoters with conserved sequence elements at ؊24 and ؊12 and utilizes specialized enhancer-binding activators to convert, through an ATP-dependent process, closed promoter complexes to open promoter complexes. The interface between 54 -RNA polymerase and promoter DNA is poorly characterized, contrasting with 70 . Here, 54 was modified with strategically positioned cleavage reagents to provide physical evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
2

Year Published

2005
2005
2008
2008

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 56 publications
4
52
0
2
Order By: Relevance
“…This is because nucleotides Ϫ78 to Ϫ63 upstream of the rpoS ORF comprise a theoretical, RpoN-dependent consensus Ϫ24/Ϫ12 promoter (33,34). Many studies with various bacteria have indicated close contact of RpoN with such a Ϫ24/Ϫ12 promoter region (5,6,21,33). However, as yet, there have been no experimental data to substantiate this prediction for B. burgdorferi.…”
mentioning
confidence: 77%
“…This is because nucleotides Ϫ78 to Ϫ63 upstream of the rpoS ORF comprise a theoretical, RpoN-dependent consensus Ϫ24/Ϫ12 promoter (33,34). Many studies with various bacteria have indicated close contact of RpoN with such a Ϫ24/Ϫ12 promoter region (5,6,21,33). However, as yet, there have been no experimental data to substantiate this prediction for B. burgdorferi.…”
mentioning
confidence: 77%
“…This can explain why ⌬1149 -1190 E 54 has reduced activity for closed complex formation. Because DNA contacts within the closed complex are exclusively made by 54 (17,19), 4 we propose that deletion of ␤Ј residues 1149 -1190 leads to repositioning of 54 domains, notably the Region I domain, which is located close to the start site-proximal consensus promoter DNA element within the closed complex (17,16,31).…”
Section: Discussionmentioning
confidence: 99%
“…DNase I and KMnO 4 Footprinting Assays-DNase I and KMnO 4 footprinting assays on closed and open complexes (formed as described above) were conducted as described (16).…”
Section: Methodsmentioning
confidence: 99%
“…This helix is primarily positively charged 54 C domain (residues Ala-335 to Gly-389). Side chains for residues that were previously shown to be near the Ϫ24 promoter element (50) and/or to decrease significantly DNA binding when mutated (48) are represented as sticks and labeled (except for Tyr-384, which is hidden behind Lys-383). All of these residues are on helix 3 (dark blue) created by the highly conserved RpoN box, except for Met-343 (Arg-421 in E. coli), which is on helix 1.…”
Section: Resultsmentioning
confidence: 99%
“…3 of 70 proteins interacts with the extended Ϫ10 promoter element near the site of melting (42,49), whereas the major role of 4 of 70 proteins is to bind to the Ϫ35 promoter element (13,15). By tethering a DNA cleavage reagent, FeBABE (p-bromoacetamidobenzyl-EDTA-Fe), to charged residues in the RpoN box of K. pneumoniae 54 , Burrows et al (50) showed that residues in the RpoN box are near the Ϫ24 promoter element, not the Ϫ12 promoter element where melting occurs. For example, with the FeBABE tethered to residue E463C (A. aeolicus Glu-386), strong cleavage was seen between the Ϫ30 and Ϫ25 nucleotides of the template DNA strand.…”
Section: Discussionmentioning
confidence: 99%